2004
DOI: 10.1175/1520-0493(2004)132<0578:teolhr>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Latent Heat Release on the Evolution of a Warm Occluded Thermal Structure

Abstract: The effect of latent heat release on the development of the occluded thermal structure in a major winter storm is examined through comparison of full physics (FP) and no-latent-heat-release (NLHR) simulations of the event performed using the fifth-generation Pennsylvania State University-NCAR Mesoscale Model (MM5). Though both simulations possess a well-developed occluded thermal ridge near the surface, the 3D structure of their respective occluded quadrants is quite different. In particular, the FP simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…14 indicates the diabatic PV tendency in the 200-150 hPa layer using the method described in Cammas et al (1994) and Posselt and Martin (2004). The explosive cyclogenesis is accompanied by strong frontogenesis, cloudband formation and strong latent-heat release (not shown).…”
Section: Large-scale Aspectsmentioning
confidence: 99%
“…14 indicates the diabatic PV tendency in the 200-150 hPa layer using the method described in Cammas et al (1994) and Posselt and Martin (2004). The explosive cyclogenesis is accompanied by strong frontogenesis, cloudband formation and strong latent-heat release (not shown).…”
Section: Large-scale Aspectsmentioning
confidence: 99%
“…These models allowed for the examination of the role of various physical processes in cyclone development, in particular, latent heat release and cloud effects on radiation. Multiple studies noted that latent heat release not only contributed to the intensity of low pressure systems and the rapidity of cyclogenesis (Smagorinski 1956;Krishnamurti 1968;Tracton 1973;Chang et al 1982;Reed et al 1988;Kuo et al 1991;Davis 1992;Whittaker and Davis 1994;Stoelinga 1996), but also acted to change the spatial patterns of surface pressure and precipitation, as well as the structure and evolution of fronts (Baldwin et al 1984;Dudhia 1993;Posselt and Martin 2004;Reeves and Lackmann 2004). It was also found that changes in the cloud effect on radiative fluxes could have a significant effect on the development of baroclinic waves.…”
Section: Dokloi I75/bams-89-5-599mentioning
confidence: 99%
“…Furthermore they showed that the negative PV anomaly developing above the maximum heating strongly modified the upper-level PV pattern and the evolution of the downstream flow. Posselt and Martin (2004) showed that the existence of an occluded thermal structure was strongly dependent on diabatic heating. These results, among others, show the potential of diabatic heating processes to influence the dynamics in complex ways.…”
Section: Introductionmentioning
confidence: 99%